Retina and Optic Disc Characteristics in Amblyopic and Non-amblyopic Eyes of Patients with Myopic or Hyperopic Anisometropia - Arzu Taşkıran Çömez (Türk Oftalmoloji Dergisi, 2017)
Objectives: To compare retinal and optic disc characteristics between amblyopic and non-amblyopic eyes in patients with myopic and hyperopic anisometropia measured with optical coherence tomography (OCT). Materials and Methods: Patients with myopic (25 patients: 17 female, 8 male; median age 27 years, range 16-40 years) and hyperopic (31 patients: 19 female, 12 male; median age 20 years, range 13-41 years) anisometropic amblyopia were included. Eye examination included determination of best-corrected visual acuity (BCVA) with a Snellen chart, measurement of manifest and cycloplegic refraction after pupillary dilation, alternate cover testing, globe movement evaluation, A-scan biometry for axial length, biomicroscopy, fundus examination, and OCT scanning. Main outcome measures were spherical equivalence, BCVA, axial length, retinal nerve fiber layer (RNFL) thickness, macular thickness, macular volume, and optic disc area. Results: In both myopic and hyperopic patients, the absolute value of the mean spherical equivalence was significantly greater in the amblyopic than non-amblyopic eyes, and the mean BCVA was significantly less in the amblyopic than the non-amblyopic eyes. In both myopic and hyperopic patients, there were no significant differences in mean RNFL thickness, macular thickness, macular volume, axial length, or optic disc area between amblyopic and non-amblyopic eyes. Conclusion: The amblyopic process may have no significant effect on the RNFL, macula, or optic disc. Further studies with more patients, including postmortem studies, may clarify the retinal, histopathologic, and anatomic differences between amblyopic and non-amblyopic eyes.